2016
DOI: 10.1038/srep30630
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Chemotherapy of Malignant Glioma in Rats by Using Multidrug-Loaded Biodegradable Nanofibrous Membranes

Abstract: Glioblastoma multiforme has a poor prognosis and is highly chemoresistant. In this study, we implanted biodegradable 1,3-bis[2-chloroethyl]-1-nitroso-urea-, irinotecan-, and cisplatin-eluting poly[(d,l)-lactide-co-glycolide] (BIC/PLGA) and virgin nanofibrous membranes on the brain surface of C6 glioma-bearing rats in concurrent and virgin groups, respectively. The concentrations of all applied drugs were significantly higher in the brain than in the blood for more than 8 weeks in all studied rats. Tumor growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…However, patients subjected to these treatments do not exceed, on average, ~15 months of survival [ 5 ]. At the same time, the incorporation of new strategies such as anti-proliferative, anti-angiogenic, and immunological therapies have not achieved a great improvement in survival rates [ 5 , 7 , 8 , 9 ], so the search for new therapeutic alternatives for GBM has become highly relevant in recent years [ 5 , 10 ]. Studies from ours and other laboratories have found that the main factor that leads to the failure of chemotherapy in GBM is the expression and activity of ATP binding cassette (ABC) transporters [ 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, patients subjected to these treatments do not exceed, on average, ~15 months of survival [ 5 ]. At the same time, the incorporation of new strategies such as anti-proliferative, anti-angiogenic, and immunological therapies have not achieved a great improvement in survival rates [ 5 , 7 , 8 , 9 ], so the search for new therapeutic alternatives for GBM has become highly relevant in recent years [ 5 , 10 ]. Studies from ours and other laboratories have found that the main factor that leads to the failure of chemotherapy in GBM is the expression and activity of ATP binding cassette (ABC) transporters [ 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, higher drug concentrations possess more efficient therapeutic effects and prevent tumour resistance. In vitro studies have shown that BCNU-resistant human glioma cells are effectively killed at a BCNU concentration of 250 lM (53.75 lg/mL) [51]. The HSNMs developed in this study released concentrations of BCNU higher than 200 lg/mL for more than 14 weeks.…”
Section: Discussionmentioning
confidence: 93%
“…Despite major developments in therapeutic interventions, GB is one of the most lethal and invasive malignancies of the central nervous system and is the leading cause of overall cancer-associated mortality. Patients with GB exhibit poor prognosis [ 26 ] and the current therapy mostly fails because these patients develop multidrug resistance and do not respond to the treatment [ 27 , 28 , 29 ]. Studies have shown that lncRNAs are widely accepted and play a crucial role in the development, progression, and metastasis of cancer as well as in drug resistance of GB.…”
Section: Discussionmentioning
confidence: 99%